Educação ambiental na escola: conscientização da necessidade de proteção contra a radiação ultravioleta - Pinheiro, Damaris Kirsch; Evangelho, Sandra de David (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2010)
This paper refers to a field research on the subject: "Environmental Education in School:Awareness of the Need for Protection Against Ultraviolet Radiation," in which I proposed to"develop educational activities with students of second year and third year high school ElementarySchool of Basic Education Francisco Brochad da Rocha, issues and environmental problems,specifically problems related to overexposure to the sun, aiming to verify: the importance ofworking with students to preserve the environment, the need to protection against ultravioletradiation and the main diseases caused by excessive exposure to the Sun Data collection wasperformed with 12 (twelve) students of second year and twelve (12) third graders EducationFundamental through semi-structured interviews and questionnaires. It is necessary to becomeaware of what to avoid mistreating the environment is to preserve the future and, from that,knowing that everybody's duty, not only perform your part, but also to educate those who arearound you.